2004
DOI: 10.1063/1.1810195
|View full text |Cite
|
Sign up to set email alerts
|

Resistance degradation due to interstitial hydrogen in photorefractive potassium lithium tantalate niobate single crystals

Abstract: Resistance degradation in potassium lithium tantalate niobate (KLTN) doped with iron and titanium was measured in a single sample containing various concentrations of interstitial hydrogen. In this crystal the degradation arose from the migration of interstitial hydrogen and not oxygen vacancies, as reported in previous research. Interstitial hydrogen and oxygen vacancy defects both arise to compensate the valence shortfall of the substitutional iron impurities and the thermodynamic balance between the two com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Through a well-designed experiment, Ivker et al found that interstitial hydrogen may fulfill the role of mobile ion usually attributed to oxygen vacancy in models of resistance degradation for perovskite-type oxides and a quantitative analysis of the competition between hydrogen and oxygen vacancy was expected. 10 Though oxygen vacancy is ubiquitous in oxide materials, now more and more works have demonstrated that hydrogen also widely exists in many oxides, and as the smallest atom, it deserves extra attention due to its high mobility. 11 In summary, hydrogen from the electrolysis of water induced two kinds of time-dependent changes in dielectric properties of barium titanate single crystals: One was characterized by continuous increases in the slope of capacitancefrequency curve and in the height of a dielectric loss peak in the course of the electrolysis of water; the other was characterized by a continuous decrease in the slope of capacitancefrequency curve and continuous decreases in both the height and the frequency of the dielectric loss peak in subsequent aging process after the electrolysis of water.…”
mentioning
confidence: 99%
“…Through a well-designed experiment, Ivker et al found that interstitial hydrogen may fulfill the role of mobile ion usually attributed to oxygen vacancy in models of resistance degradation for perovskite-type oxides and a quantitative analysis of the competition between hydrogen and oxygen vacancy was expected. 10 Though oxygen vacancy is ubiquitous in oxide materials, now more and more works have demonstrated that hydrogen also widely exists in many oxides, and as the smallest atom, it deserves extra attention due to its high mobility. 11 In summary, hydrogen from the electrolysis of water induced two kinds of time-dependent changes in dielectric properties of barium titanate single crystals: One was characterized by continuous increases in the slope of capacitancefrequency curve and in the height of a dielectric loss peak in the course of the electrolysis of water; the other was characterized by a continuous decrease in the slope of capacitancefrequency curve and continuous decreases in both the height and the frequency of the dielectric loss peak in subsequent aging process after the electrolysis of water.…”
mentioning
confidence: 99%